Fluid therapy in mechanically ventilated critically ill children: the sodium, chloride and water burden of fluid creep - Thomas Langer; Veronica D'Oria; Giulia C. I. Spolidoro; Giovanna Chidini; Stefano Scalia Catenacci; Tiziana Marchesi; Marta Guerrini; Andrea Cislaghi; Carlo Agostoni; Antonio Pesenti; Edoardo Calderini (BMC, 2020)
Abstract Background Fluid therapy is a cornerstone of pediatric intensive care medicine. We aimed at quantifying the load of water, sodium and chloride due to different fluid indications in our pediatric intensive care unit (PICU). We were particularly interested in the role of fluid creep, i.e. fluid administered mainly as the vehicle for drugs, and the association between sodium load and water balance. Methods Critically ill children aged ≤3 years and invasively ventilated for ≥48 h between 2016 and 2019 in a single tertiary center PICU were retrospectively enrolled. Need for renal replacement therapy, plasmapheresis or parenteral nutrition constituted exclusion criteria. Quantity, quality and indication of fluids administered intravenously or enterally, urinary output and fluid balance were recorded for the first 48 h following intubation. Concentrations of sodium and chloride provided by the manufacturers were used to compute the electrolyte load. Results Forty-three patients (median 7 months (IQR 3-15)) were enrolled. Patients received 1004 ± 284 ml of water daily (153 ± 36 ml/kg/day), mainly due to enteral (39%), creep (34%) and maintenance (24%) fluids. Patients received 14.4 ± 4.8 mEq/kg/day of sodium and 13.6 ± 4.7 mEq/kg/day of chloride, respectively. The majority of sodium and chloride derived from fluid creep (56 and 58%). Daily fluid balance was 417 ± 221 ml (64 ± 30 ml/kg/day) and was associated with total sodium intake (r2 = 0.49, p < 0.001). Conclusions Critically ill children are exposed, especially in the acute phase, to extremely high loads of water, sodium and chloride, possibly contributing to edema development. Fluid creep is quantitatively the most relevant fluid in the PICU and future research efforts should address this topic in order to reduce the inadvertent water and electrolyte burden and improve the quality of care of critically ill children.